Pre-operative ultrasound localization of misdiagnosed foreign object as verruca vulgaris: a case report - Ying Lan; Junqiu Xiang; Yiling Ma; Dong Xiao (Journal of Dermatological Treatment)
Aim Verruca vulgaris is a common skin disease among children. Foreign object mimicking a wart is unusual.Methods A report of a 6-year-old boy with foreign object misdiagnosed as verruca vulgaris.Results Ultrasound was used to locate and mark the foreign object pre-operatively. Surface and infiltration anesthesia combination was used before removing the foreign object within 5 min. The patient was followed up 1.5 months post-operatively; the wound was healed without obvious scar.Conclusions Compared to dermatoscopy, ultrasound has advantages in diagnosing foreign objects. Preoperative ultrasound can provide useful information for identifying and removing foreign objects.